A new species of Pachycerianthus (cnidaria, Anthozoa, Ceriantharia) from Tropical Southwestern Atlantic - Stampar, Sérgio Nascimento [UNESP]; Morandini, André Carrara; Silveira, Fabio Lang da (Magnolia Press, 2014)
A new species of Pachycerianthus (Cnidaria: Ceriantharia) is described from the Brazilian coast of the southwestern Atlantic Ocean. Pachycerianthus schlenzae sp. nov. is found in fine sand or mud in shallow waters of Abrolhos and Royal Charlotte Bank. The new species is only known from this area and is most notably different from other species of the genus Pachycerianthus in mesentery arrangement and cnidome. In addition to the description, we provide some biological data collected from individuals cultivated under laboratory conditions.
Keywords: Systematics; DNA Barcoding; Morphology; Cerianthidae; Cnidaria; taxonomia; Sistemática; Zoologia; DNA Barcoding